Assessing Bolus Retention in Achalasia using High Resolution Manometry with Impedance: A Comparator Study with Timed Barium Esophagram - Cho, Yu K. (Am J Gastroenterol, 2014)
BACKGROUND: The aim of this study was to assess whether high-resolution impedance-manometry (HRIM) could be utilized to assess bolus retention similar to the timed barium esophagram (TBE). METHOD: 20 achalasia patients [10 males, ages 21–79] were prospectively evaluated with HRIM and TBE to determine the correlation between barium column height and the impedance bolus height (IBH). The TBE protocol utilized a 200 ml barium challenge and the HRIM protocol utilized a 200 ml saline challenge protocol. Both protocols were performed in an upright position and the heights of the barium and impedance columns were measured at 1 and 5 minutes. Analysis of IBH was performed with a topographic technique and a spatial impedance variation plot. RESULTS: There was no significant difference between the median IBH and barium column at 1 minute [IBH 12.0 cm (IQR, 8.0–18.0), TBE 12.0 cm (IQR, 7.0–19.0), P=0.90] or 5 minutes [IBH 11.0 cm (IQR, 1.0–17.0), TBE 9.0 cm (IQR, 4.0–12.0), P=0.47]. Additionally, the correlation between the two measurements at 1 and 5 minutes was 0.60 and 0.86, respectively. Using a barium column or impedance height of >5.0 as a definition of bolus retention was associated with 75% concordance at 1 minute and 95% concordance at 5 minutes. CONCLUSION: There was excellent agreement between TBE and HRIM for assessing bolus retention at 5 minutes. Thus, HRM with impedance may be utilized as a single test to assess bolus retention and motor function in the management of achalasia.